Socio-Religious Movement: MPTT-I in the Spread of Tasawuf Tauhid in South Aceh - Samwil, Samwil; Khairan, Khairan; Tjoetra, Afrizal; Saputra, Akmal (Journal of Social and Policy Issues, 2026)
This study aims to explain the resource mobilization strategies used by the Indonesian Tauhid Tasawuf Study Council (MPTT-I) in spreading Sufism teachings in South Aceh and its ability to survive amidst resistance from mainstream religious authorities. The study employed a descriptive qualitative method, collecting data through in-depth interviews, observations of da'wah activities, and documentation studies. Data analysis was conducted through interactive data reduction, presentation, and conclusion drawing techniques, and validity was strengthened by triangulation of sources and methods. The results indicate that the successful development of MPTT-I is supported by the utilization of material resources such as da'wah facilities and voluntary support from the congregation, as well as human resources through cadre structures and charismatic leadership. Furthermore, symbolic capital and social networks, including the use of digital media, play a significant role in strengthening the movement's legitimacy and expanding its support base. MPTT-I is also responsive to criticism and competition from religious authorities at the local level. In conclusion, MPTT-I is able to combine traditional da'wah practices with modern organizational strategies, thus maintaining its existence and development within the socio-religious dynamics of South Aceh. These findings emphasize the importance of resource mobilization for the sustainability of socio-religious movements in Indonesia.